Low-temperature solution-processed wavelength-tunable perovskites for lasing - Xing, Guichuan (2014)
Low-temperature solution-processed materials that show optical gain and can be embedded into a wide range of cavity resonators are attractive for the realization of on-chip coherent light sources. Organic semiconductors and colloidal quantum dots are considered the main candidates for this application. However, stumbling blocks in organic lasing include intrinsic losses from bimolecular annihilation and the conflicting requirements of high charge carrier mobility and large stimulated emission; whereas challenges pertaining to Auger losses and charge transport in quantum dots still remain. Herein, we reveal that solution-processed organic–inorganic halide perovskites (CH3NH3PbX3 where X = Cl, Br, I), which demonstrated huge potential in photovoltaics, also have promising optical gain. Their ultra-stable amplified spontaneous emission at strikingly low thresholds stems from their large absorption coefficients, ultralow bulk defect densities and slow Auger recombination. Straightforward visible spectral tunability (390–790 nm) is demonstrated. Importantly, in view of their balanced ambipolar charge transport characteristics, these materials may show electrically driven lasing.